2016
DOI: 10.1038/srep33549
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines release the let-7b-mediated suppression of initiation codon recognition during the protein synthesis of EXT2

Abstract: Proteoglycans (PGs), a family of glycosaminoglycan (GAG)-protein glycoconjugates, contribute to animal physiology through interactions between their glycan chains and growth factors, chemokines and adhesion molecules. However, it remains unclear how GAG structures are changed during the aging process. Here, we found that polyamine levels are correlated with the expression level of heparan sulfate (HS) in human skin. In cultured cell lines, the EXT1 and EXT2 enzymes, initiating HS biosynthesis, were stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…Microscale isolation of glycosaminoglycans (GAGs) was performed using an anion exchange spin column with minor modifications (Imamura et al 2016). Brain tissues were lyophilized until they were dry.…”
Section: Disaccharide Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Microscale isolation of glycosaminoglycans (GAGs) was performed using an anion exchange spin column with minor modifications (Imamura et al 2016). Brain tissues were lyophilized until they were dry.…”
Section: Disaccharide Analysismentioning
confidence: 99%
“…Unsaturated disaccharide analysis was conducted with reverse phase ion-pair chromatography using sensitive and specific postcolumn detection (Imamura et al 2016).…”
Section: Disaccharide Analysismentioning
confidence: 99%
“…As a result, it was found that syntheses of EXT1 and EXT2 were enhanced by polyamines at the level of translation (Fig. 3A) (10).…”
Section: Nm)mentioning
confidence: 87%
“…The distribution and number of protein-binding sites containing IdoA and di-sulfated disaccharides in the GAG chains are also important for the interaction with the GAG-binding proteins including ATIII or receptor-type protein tyrosine phosphatase PTPRσ (2,6). Therefore, GAG biosynthesis by glycosyltransferases, sulfotransferases, and C5 epimerase is intricately regulated at multiple levels in mammals as the degree of sulfation and GAG C5 epimerization are both tissue-and cell type-specific (7)(8)(9)(10)(11). There are several reports describing that the ratio of the 4-O-sulfation and 6-Osulfation (4S/6S) in CS disaccharides, changed during the normal embryonic development, growth, and aging (12)(13)(14)(15)(16).…”
Section: A Introductionmentioning
confidence: 99%
“…Klf4 has a long GC-rich 5 0 -UTR, one of the characteristics of genes regulated by polyamines at the translational level. Several mechanisms of polyamine mediated stimulation of translation have been reported, such as ribosome shunting on the 5 0 -UTR [8], distant positioning of the CR sequence from the AUG [29], frameshifting at the termination codon (UGA) on the ORF [36], and miRNA mediated suppression of initiation codon recognition [37]. In this study, to clarify the mechanism of translational stimulation of KLF4 by polyamines, we used luciferase reporter plasmids containing several 5 0 -UTR versions of Klf4 mRNA.…”
Section: Discussionmentioning
confidence: 99%